Identifying and Utilizing Local Potentials in Rubiah Island as a Biology Learning Resource - Anita Noviyanti; Dian Aswita; Dewi Febriyanti; Sri Ismulyati (Postgraduate, University of Mataram, 2025)
This research focuses on exploring the various benefits of integrating local potential into biology learning to enhance conceptual understanding, student engagement, improve thinking skills, change behavior, and environmental awareness. The aim of this study is to provide a comprehensive analysis of how the potential of local biodiversity in coral reef ecosystems can be effectively integrated into biology learning. The method used was an exploratory descriptive study. The research was conducted on Rubiah Island. Data collection techniques included direct observation and literature review. The data obtained were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that local potential coral reefs can be utilized as learning resources through their utilization. They do not require special design and can be directly applied and used in the learning process. Integrating local potential into biology learning offers promising opportunities for innovative and engaging learning experiences. The material related to this utilization is biodiversity, including species diversity, the benefits and value of biodiversity, the classification of living things, animals, ecology, and environmental change. The conclusion of this study indicates that the utilization of local potential can enrich the reference sources for biology learning while providing a positive impact on environmental sustainability.